1997
DOI: 10.1002/aic.690431112
|View full text |Cite
|
Sign up to set email alerts
|

Model for surface diffusion in liquid‐phase adsorption

Abstract: Based on the absolute-rate theoly, a consistent interpretation was provided for the dependence of surface-difiion coeffiient, D,, on temperature and the amount adsorbed in various liquid-phase adsorption systems, such as the Langmuir-, Freundlichand Jossens-type adsorption. It was demonstrated that a restricted molecular diffusion model for surface diffusion was useful for the analysis of the characteristic features of 0,. A formulation of D, was derived based on the model and was applied to the analysis of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Previously, , we analyzed the correlation between D s and the parameters of the retention process, i.e., K and Q st , and developed the restricted diffusion model as an approximation of the mechanism of surface diffusion. Surface diffusion was regarded as molecular diffusion restricted by the adsorptive interactions between the adsorbate molecules and the surface of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, , we analyzed the correlation between D s and the parameters of the retention process, i.e., K and Q st , and developed the restricted diffusion model as an approximation of the mechanism of surface diffusion. Surface diffusion was regarded as molecular diffusion restricted by the adsorptive interactions between the adsorbate molecules and the surface of the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…However, it allows the increasing trend in diffusivities with increasing concentrations to be explained. Recently, Miyabe and Takeuchi have discussed the dependence of surface diffusivities or temperature and concentration, as a function of isotherm type . For a Langmuir-type isotherm, the concentration dependence of surface diffusivity is interpreted in terms of change (d ln C e /d ln q ), independently of the adsorption potential, while for a Freundlich-type isotherm, surface diffusivities vary with the isosteric heat of adsorption, but independently of the change in the logarithmic slope of the adsorption isotherms (d ln C e /d ln q ).…”
Section: Resultsmentioning
confidence: 99%
“…A consistent interpretation was provided for both temperature and concentration dependence of D s in various liquid-phase adsorption systems, such as the Langmuir, Freundlich, and Jossens type adsorption. Irrespective of the type of adsorption systems, the dependence of D s on q could be interpreted by taking into account the variation of both the logarithmic slope of an adsorption isotherm, d ln c/d ln q, and adsorption potential, E ap (Miyabe and Takeuchi, 1997b). It was also demonstrated that the various correlations between E s and Q st could be quantitatively explained by the model (Miyabe and Takeuchi, 1997a).…”
Section: Introductionmentioning
confidence: 99%